PASAR KERJA FLEKSIBEL VERSUS PERLINDUNGAN PEKERJA DI INDONESIA - Zantermans Rajagukguk (Jurnal Kependudukan Indonesia, 2010)
Some empirical studies have tried and showing that labor market in most of countries outside of Europe and USA, are inflexible, or rigid. One of the most relevant causes is connected with rigidities of employment protection legislation (EPL). Theoretically it said that any kind of EPL will prevent employers to hiring and .firing employee. So, to create LMF, an argument which is raised is addressed to abolish EPL. This paper aimed to suggests the analysis of (1) the impact of applying the concept of LMF connected with the employment protection in Indonesia, especially those related to wages, employment status, trade union, and layoffs, (2) the most appropriate form of LMF due to Indonesia s conditions. This paper is part of the review on "The Impact of Labor Market Flexibility against Employment Protection in Indonesia", by taking a sample of 125 companies in various sectors. The analytical method used is explanatory. The .findings of the study results indicate that, it is too hard for Indonesia to implement LMF presently due to several causes: (1) LMF concept contain many controversy and never defined very precisely or directly; (2) insufficient conditions required, such as low level of Indonesia's IDV Index, unemployment rates is still high and persistent, weak of employee bargaining power in employment relationships; and (3) corporate culture. If LMF implemented currently, or while requirements have not yet been filled, it will call negative influence to the employment protection, because: (1) creating employer aristocrat; (2) pushdown employee to the lowest level; (3) creating Hobbesian contract; and (4) eliminating government functions. At present, the most relevant issues should be considered is to develop a more realistic and an ideal LMF concept, that has to be made some trade-off probably between LMF and employment protection, that allow an opportunities to increasing enterprises competitive power and ensuring employment protection minimum standard at the same time. For Indonesia, may be now is the time to implementing wages based on productivity system accompanied by creating an unemployment insurance benefits for employee(s) who dismissed. Based on concluding remarks above, this paper suggested employers, employees, and government, and experts should sit side by side to develop an ideal LMF concept for Indonesia, accompanied by increasing economic performance, pushdown rates of unemployment to the average level of the natural rates of unemployment. Besides, employers should prepare to justify their corporate culture by implementing "mental and ideological approach", which is not just to hunting profit, but ready to pay "cost of change" also. Last but not least, trade unions should more professional and independent, both as a closer partner of employer and as a employees representation.